Afrontamiento del Prejuicio de Género en Las Personas Trans y No Binarias en Santiago de Chile: Comparaciones Clínicas y Despliegues Identitarios - Aviles-Gonzalez, B (UNIV CHILE, FAC CIENCIAS SOCIALES, 2024)
In Chile, non-binary people have been invisible by the sex-gender system, being homologated in the trans binary category, which makes it difficult to understand their subjective and identity experiences. This study seeks to know and differentiate how trans (binary) people and nonbinary people from Santiago de Chile respond to gender bias, identifying the effects on identities and psychological. The population was made up of binary, non-binary trans people and health professionals who work with these populations. A total of 22 people participated in four focus groups and 15 individual semi-structured interviews. After an analysis using Grounded Theory, an explicit prejudice towards trans binary people and a mostly symbolic prejudice towards non-binary people is identified. There are differences in the strategies for coping with prejudice, although at the psychotherapeutic level similar symptomatic and clinical expressions are reported: depression, anxiety, hopelessness and suicidal ideation.